Laser – induced donor centers in p-InSb - Fedorenko, L.; Medvid, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The laser – induced donor centers in p-Insb have been studied by magneto-concentration effect (MCE). The distribution of donor centers in the nonequilibrium temperature field in InSb was obtained by redistribution of the interstitial In atoms (IIn) and vacanciens VIn under laser action. Comparison of the theoretical calculation and experimental data showed that depth δ of the position of p-n junction increased with temperature, and that relatively large value of δ at used value of laser intensity (Р ~ 3.5 MW/cm²) is connected with presence of liquid phase during laser annealing process. Obtained results correlate with Atomic Force Microscopy (AFM) measurements. Experiments were performed on p-InSb samples in the temperature range 180–290 K. Temperature gradient was provided by YAG: Nd laser illumination (l = 0.53 µm, t = 15 ns). The laser donor centers (LDC) of two kinds were found: one is nonstable and annealed at room temperature with relaxation constant ~ 5 s, and the other is stable, annealed at temperature 670 K. The threshold of LDC formation is 1.5 MW/cm². The activation energy of the stable donor centers is 1,1 eV. Investigation of the surface morphology by AFM in dependence on the intensity of laser radiation showed a good agreement with obtained results.